Overlay multicast strategy based on utility optimization for wireless mesh networks - ZHU Cui-tao1; YANG Zong-kai1; CHENG Wen-qing1; WU Di1; YAN He 1 (Tongxin xuebao)
Multicast support is a critical and desirable feature of wireless mesh network（WMN）.A distributed algorithm was presented based on pricing scheme by using Lagrange dual decomposition technique.According to the algorithm to joint optimizing rate allocation of flows and power consumption of links for forwarding data flows,to maximize the net utility.The price is associated with each individual network link,which reflects the traffic load on this link.The flow in turn collects the prices of all links on its multicast path and calculates the overall network price,then adjusts the stream-ing rate.The validity and effectiveness of the approach are demonstrated in simulations.